2013
DOI: 10.1016/j.jfs.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TARP on bank risk-taking

Abstract: ABSTRACT:One of the largest responses of the U.S. government to the recent financial crisis was the Troubled Asset Relief Program (TARP). TARP was originally intended to stabilize the financial sector through the increased capitalization of banks. However, recipients of TARP funds were then encouraged to make additional loans despite increased borrower risk. In this paper, we consider the effect of the TARP capital injections on bank risktaking by analyzing the risk ratings of banks' commercial loan originatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(114 citation statements)
references
References 30 publications
7
102
2
Order By: Relevance
“…Forssbaeck (2011) also explores the importance of deposit insurance and ownership on bank risk-taking but his work differs from ours along several dimensions. For instance, his paper focuses on the period from 1995 to 2005, and in contrast to our findings, 3 In related work, other authors have found a positive effect of actual government support on bank risk-taking (see Black and Hazelwood, 2012, for the effect of TARP on U.S. banks and Duchin and Sosyura (2011) for a broader sample of U.S.publicly traded financial firms). We instead focus on expected, not actually received, government support and use a sample of banks from many countries.…”
contrasting
confidence: 95%
“…Forssbaeck (2011) also explores the importance of deposit insurance and ownership on bank risk-taking but his work differs from ours along several dimensions. For instance, his paper focuses on the period from 1995 to 2005, and in contrast to our findings, 3 In related work, other authors have found a positive effect of actual government support on bank risk-taking (see Black and Hazelwood, 2012, for the effect of TARP on U.S. banks and Duchin and Sosyura (2011) for a broader sample of U.S.publicly traded financial firms). We instead focus on expected, not actually received, government support and use a sample of banks from many countries.…”
contrasting
confidence: 95%
“…Bagehot (1873) already noted the moral hazard e ect and excessive risk-taking induced by banks' expectation for bailout (instead of resolution). Although various rationales for bailout policies can be formulated (Acharya and Yorulmazer, 2007;Diamond and Dybvig, 1983;Diamond and Rajan, 2005), several recent studies provide empirical evidence regarding the moral hazard e ect of bailout (expectations) on risk-taking (e.g., Black and Hazelwood, 2013;Dam and Koetter, 2012;Duchin and Sosyura, 2013). Conversely, when bailout guarantees cease to be implicit through a credible and enforceable improvement in bank resolution regimes, we expect banks to change their behavior towards less risk-taking.…”
Section: )mentioning
confidence: 95%
“…Our paper contributes to the recent literature on the e ects of regulatory actions on bank behavior, particularly risk-taking (e.g., Berger et al, 2012;Black and Hazelwood, 2013;Dam and Koetter, 2012;Duchin and Sosyura, 2013). Whereas these papers focus primarily on the e ects of government bailout policies, we investigate the e ects of an ex ante disciplining regulatory approach.…”
Section: )mentioning
confidence: 98%
See 1 more Smart Citation
“…While the eects of various bailout mechanisms and accommodative policies, such as recapitalization, blanket guarantees, and regulatory forbearance have recently attracted a lot of attention (Black and Hazelwood, 2012;Dam and Koetter, 2012;Giannetti and Simonov, 2011;Honohan and Klingebiel, 2003;Laeven and Valencia, 2011), there is still a lack of conclusive empirical evidence on the real eects of strict implementation of insolvency and resolution regimes.…”
Section: Non-technical Summarymentioning
confidence: 99%